Simply InGEN(E)ious! How Creative DNA Modeling Can Enrich Classic Hands-On Experimentation - Julia Mierdel (American Society for Microbiology, 2020)
Innovative 21st-century methods for teaching biology should provide both content knowledge and diverse scientific competencies. The Curriculum Guidelines of the American Society for Microbiology highlight the importance of developing scientific thinking skills, which include the abilities to formulate hypotheses, to communicate fundamental concepts effectively, and to analyze and interpret experimental results. Additionally, contemporary science education should enhance creativity and collaboration as key student assets in its bid to overcome negative perceptions and learning difficulties. In recent years, the expanding movement for so-called “STEAM” approaches (science, technology, engineering, arts, and math) has increased in STEM curricula. The movement seeks to integrate the arts into science classes to transfer enthusiasm, support individual self-sufficiency, and encourage creative solutions. To meet all these demands, we developed an inquiry-based approach that actively engages students in hands- and minds-on activities on the topic of “decoding the DNA structure” in an outreach laboratory. Since teaching abstract molecular phenomena is a challenge in biology classes, we combine classical experimental tasks (DNA isolation, gel electrophoresis) with creative modeling. The experiments are linked by the modeling phase: immersed in the story of the discovery of the DNA structure, our participants independently construct a DNA model from a box filled with inexpensive craft supplies (e.g., glue, straws, pipe cleaners, beads). After initial pilot testing, the implementation of our approach clearly produced short- and mid-term learning effects among the students, providing a successful example of a STEAM-based approach in a laboratory setting.